117PShort-term and long-term outcomes of hepatectomy combined with intraoperative radiofrequency ablation for multiple colorectal liver metastases: A propensity score matching study. (24th November 2019) - Huang, W; Chen, Y; Chang, W; Wei, Y; Xu, J
Abstract: Background: Radiofrequency ablation (RFA) helps to achieve R0 resection and may provide an alternative treatment for patients with unresectable colorectal liver metastases (CRLM) in combination with surgical resection. However, researches on efficacy and complication risks of hepatectomy combined with intraoperative RFA for multiple colorectal liver metastases (mCRLM) are limited. Methods: From January 2013 and March 2017, patients who underwent hepatectomy alone (HA cohort) or hepatectomy combined with intraoperative RFA (HIR cohort) for mCRLM were retrospectively identified from Zhongshan Hospital affiliated to Fudan University. The mCRLM patients that were given 'hepatectomy combined with intraoperative RFA' were matched with those treated with hepatectomy alone via 1:1 propensity score (PS) matching. Recurrence-free survival (RFS) and overall survival (OS) after the initial hepatectomy were compared. Results: After PSM, 252 patients were included (126 in each group). The HIR cohort had more grade I complications while no difference in higher grade complications (p = 0.231) and postoperative morbidity(p = 0.534) was detected. Total recurrence which includes intrahepatic and extrahepatic recurrence was no significantly difference in HIR cohort compared to HA cohort (p = 0.320). The median total RFS for HIG and HA was 10.47months and 10.7 months respectively (HR = 1.086 95% CI 0.766-1.540). The median OS for HIG and HA was 43.9 months and 46.1 months respectively (HR = 0.986 95% CI 0.648-1.307). Conclusions: Hepatectomy combined with intraoperative RFA can be safely performed in mCRLM patients without an increased severe risk in the procedure and is representing a beneficial treatment to otherwise inoperable patients. The outcome of hepatectomy combined with intraoperative RFA is even comparable to hepatectomy alone after propensity score matching. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.